The diversity of lichens along elevational gradients in the Tropical Montane Forest of Selangor, Malaysia - Azlan Abas,; Laily Din, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study aims to explore how lichen diversity, composition, and distribution vary with altitude, and environmental factors (temperature and relative humidity). The study was conducted in the forest of Gunung Bunga Buah, Selangor at five sites (different altitudes). Forty-four lichen species were identified. Their diversity, composition, and distribution correlated significantly with the altitude and environmental factors, increasing diversity at higher altitudes. Graphidaceae and Physciaceae species were present at all altitudes, and the dominant species changed according to altitude: Some Parmeliaceae species were found only at higher altitudes (601-1430 m) while Chrysothrix xanthina and a few Physciaceae species were present only at lower altitudes (0-600 m). These findings will provide additional information about the lichens of the tropical montane forest of Malaysia to enhance knowledge on how to manage and sustain lichens in this type of forest.